Obscene Theming as Strategic Commodification of Public Spaces: Analyzing the Material Outcomes of Staging Sexualized Feminine Bodies in Venice Beach - Pires, Alexandre (ACME, 2026)
The provocative display of feminine sexuality is a defining feature of many mainstream tourist destinations. In Venice Beach, such displays adopt a countercultural aesthetic while serving the interests of its private tourist economy. I argue that the sexualized staging of feminine bodies contributes to the obscene theming of public spaces—a mode of spatial production in which capitalist logics aestheticize, commodify, and ultimately privatize public spaces. Obscene theming operates through the aesthetic production of feminine bodies, which are incorporated into tourist imaginaries and fantasies of democratic freedom associated with Venice Beach. Drawing on Lukács’s theory of commodification, I contend that this staged obscenity functions to reinforce spatial injustices. It masks the labor involved in producing these embodied aesthetics by framing them as expressions of individual agency, while enabling a normative tourist economy that categorizes, hierarchizes, and regulates embodied performances of aesthetic transgression. I use obscenity as an analytical lens to examine how ludic culture operates within public spaces shaped by the visible stigmas of a maximally unjust urban context.